Penerapan Terapi Range Of Motion (ROM) Pada Pasien Stroke Iskemik Di Wilayah Kerja UPT Puskesmas Medan Sunggal - Fira Azhara; Afiatika Ahsani (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Background: Ischemic stroke is an acquired brain injury caused by blockage of blood vessels or inadequate blood supply resulting in infarction or hemorrhage in the brain parenchyma. Stroke is ranked as the second leading cause of death in the world and is the largest contributor to disability, resulting in a significant economic burden. The problem that often arises in ischemic stroke patients is the presence of a problem in the limbs so that the individual's ability to move cannot be free and limited which is commonly referred to as the problem of physical mobility disorders. Ischemic stroke is part of cardiovascular disease which is classified as a catastrophic disease because it has a wide economic and social impact. Ischemic stroke can cause permanent disability which can certainly affect the productivity of the sufferer. Purpose: Knowing the results of the application of Range Of Motion (ROM) exercises on the patient's muscle strength. Methods: Using case studies and subjects by collecting data from interviews and observations on Ischemic Stroke patients with nursing problems of Physical Mobility Disorders. Results: after carrying out Range Of Motion (ROM) therapy nursing actions on a routine schedule twice a day morning and evening for 6 days with 15-20 minutes, it was found that there was an increase in muscle to 4 5 4 5. Conclusion: there is an increase in muscle strength in Ischemic Stroke patients after Range Of Motion (ROM) therapy.